Masculinity Representation in the Movie “Miracle in Cell No. 7” Based on Sociology of Literature Perspective - Basid, Abdul; Amrillah, Fahimatul (Pascasarjana Universitas Negeri Semarang, 2018)
This paper aims to analyze the representation of a father's masculinity in the movie Miracle in Cell No. 7 with the causes and impacts on his daughter and the surrounding society. This analysis uses sociology and literature perspective that view literature as a portrait of social reality. This research uses descriptive qualitative method to analyze the sources of information and data from literary works. Based on the analysis found the form, cause and impact masculinity representation of father in movie Miracle in Cell No. 7. The represented form is a responsible father, willing to sacrifice and a caring and protective character. The causes of the masculine representation are father’s who loves his daughter and his helpful character. While the positive impact toward his daughter and the society are the child who loves her father, forming independent character and maturing his daughter, getting sympathy from the surrounding society and the negative impact is getting scorn and fraud.